Solve for y -3y-15=-6(y+7)

Math
-3y-15=-6(y+7)
Simplify -6(y+7).
Tap for more steps…
Apply the distributive property.
-3y-15=-6y-6⋅7
Multiply -6 by 7.
-3y-15=-6y-42
-3y-15=-6y-42
Move all terms containing y to the left side of the equation.
Tap for more steps…
Add 6y to both sides of the equation.
-3y-15+6y=-42
Add -3y and 6y.
3y-15=-42
3y-15=-42
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Add 15 to both sides of the equation.
3y=-42+15
Add -42 and 15.
3y=-27
3y=-27
Divide each term by 3 and simplify.
Tap for more steps…
Divide each term in 3y=-27 by 3.
3y3=-273
Cancel the common factor of 3.
Tap for more steps…
Cancel the common factor.
3y3=-273
Divide y by 1.
y=-273
y=-273
Divide -27 by 3.
y=-9
y=-9
Solve for y -3y-15=-6(y+7)

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top